Alarm call‐based discrimination between common cuckoo and Eurasian sparrowhawk in a Chinese population of great tits. (9th June 2017) - Yu, Jiangping; Xing, Xiaoying; Jiang, Yunlei; Liang, Wei; Wang, Haitao; Møller, Anders Pape
Abstract: Morphological resemblance of the common cuckoo Cuculus canorus to the Eurasian sparrowhawk Accipiter nisus has been regarded as an example of predator mimicry. Common hosts could distinguish parasites as the result of coevolution, while rare hosts or non‐hosts may mistake cuckoos for hawks because rare hosts or non‐hosts behave similarly when faced with these two species. Birds usually produce alarm calls in addition to showing behavioral responses when in danger. However, previous studies of identification by rare hosts or non‐hosts of sparrowhawks usually lacked experimental evidence of alarm calls. Great tits Parus major, a rare cuckoo host, perform similar behaviors and usually produce alarm calls in response to sparrowhawks and common cuckoos. Here, we tested whether great tits could distinguish common cuckoo from sparrowhawk based on analysis of their alarm calls and the effects of playback of alarm calls on conspecific behavior. Previous studies showed that great tits have a complex communication system that conveys information about predators, and they could perform different kinds of response behavior to different alarm calls. If great tits have not made the ability to distinguish between common cuckoo and sparrowhawk, then their acoustic responses to these two species and their response behaviors in playback experiments should be similar. Specimens of a common cuckoo (parasite), a sparrowhawk (predator) and an Oriental turtle dove Streptopelia orientalis (harmless control) were used to elicit and subsequently record the response behavior and alarm calls of great tits. There was no significant difference in behavioral response among great tits when exposed to the dummy of cuckoo, sparrowhawk and dove. In contrast, they differed significantly in alarm calls. Great tits produced more notes per call that contained increasing D‐type and decreasing I‐type notes when responding to sparrowhawk as compared to cuckoo or dove. In playback experiments, we found that great tits responded more strongly to great tit hawk than to great tit cuckoo or great tit dove alarm calls. Our study suggests that great tits are able to distinguish sparrowhawks from common cuckoos and convey relevant information in alarm calls by adjusting the number and combinations of notes of a single call type.